A comparative analysis of long-term spatiotemporal variability in precipitation 85 year-long reanalysis and observation data from 150 stations over arid MENA-T region - Othman, Nariman Yahya; Ayat, Berna (SPRINGER WIEN, 2026)
In this study we analyzed variability of precipitation patterns all over The Middle East and North Africa and T & uuml;rkiye (MENA-T) based on in-situ data from 150 stations and hourly ERA5 reanalysis data with the spatial resolution of 0.25 degrees x 0.25 degrees. The study period covers 85 years between 1940 and 2024. Long-term variability of 13 duration, magnitude, intensity, and frequency-based precipitation indices are mapped to reveal the spatial characteristics. Results indicated that reanalysis data are capable of hindcasting in-situ precipitation data with an overall average correlation coefficient of 0.72 (varying between 0.56 and a maximum of 0.82 among all 150 stations). The results highlight a distinct north-south dipole in precipitation trends across the region. Duration-based indices reveal a significant increase in consecutive dry days across the southwestern Arabian Peninsula, Libya, southern Algeria, and northern Egypt signaling a trend toward intensifying aridity in these already dry areas. Conversely, northern coastal and mountainous zones show decreasing dry spell durations, reflecting a shift toward more frequent or prolonged wet periods. Magnitude-and intensity-based indices, such as annual total wet-day precipitation, precipitation from very wet days more than 95%, and maximum 1-day precipitation indicate an increase in extreme rainfall in the wetter northern regions, particularly in T & uuml;rkiye, Iran, and Iraq. In contrast, these indices exhibit declining trends across southern MENA-T. Similarly, frequency-based indices show a reduction in wet-day occurrences across arid zones, while the Mediterranean and highland regions display modest increases, suggesting growing disparities in regional hydroclimatic behavior under ongoing climatic shifts.
Keywords: Precipitation; Long-term trend; Indices; MENA region; Regional analysis; DAILY TEMPERATURE; EXTREME INDEXES; MIDDLE-EAST; TRENDS; BASIN; Meteorology & Atmospheric Sciences